Interdepartmental conflict: The neglected dimension of management - B. J. Bloch (South African Journal of Business Management, 1985)
Both the theory and practice of management reflect an overemphasis on the relationships and conflicts within, rather than between such departments as personnel, finance, marketing, and production. The lateral dimension of management which refers to interdepartmental relationships, is not given adequate treatment. This article therefore deals with interdepartmental conflict - its causes and possible solutions. The article is divided into three sections. Firstly, the organizational and behavioural causes of interdepartmental conflict are examined. This refers to the inherent tendency towards conflict created by the balance between autonomy and interdependence of departments in large organizations. Secondly, conflict at departmental interfaces is discussed, i.e. the specific divergences in attitude, perceptions and activities between the most significant pairings of departments, e.g. the relationship between marketing and finance departments. Finally, techniques and imperatives for the minimization of interdepartmental conflict are outlined. Various socio-psychological techniques are described as well as the major elements of management practice needed to resolve conflict at departmental interfaces.
Keywords: 650